Use of different epoxide ring openers and volumes of epoxidized palm oil to modify palm oil into biopolyol - Neswati; Nazir, Novizar; Arief, Syukri; Yusniwati (Agriculture and Natural Resources, 2024)
Importance of the work: Epoxide ring openers and the volume of epoxidized palm oil are the most influential factors on the hydroxyl number. Objectives: To investigate the effects of three types of epoxide ring opener and varying volumes of epoxidized palm oil on the production of biopolyol. Materials & Methods: This study used 10 mL, 20 mL or 30 mL of epoxidized palm oil reacted with 30 mL of different epoxide ring openers (ethylene glycol, propylene glycol and distilled water) and added 1% sulfuric acid catalyst at 50°C for 1 hr. Biopolyol was characterized based on the hydroxyl number and Fourier-transform infrared spectroscopy (FTIR). Results: The optimum results for biopolyol as raw material for flexible polyurethane foam were a mixture of 10 mL of epoxidized palm oil with 30 mL of ethylene glycol, based on mean ± SD values for: hydroxyl number (99.37±7.27 mg KOH/g), acid number (1.19±0.1 mg KOH/g), viscosity at 30°C (46.10±6.45 cP) and density at 30°C (0.906±0.009 g/mL) and a clear yellow color. A wave number of 3332.05/cm in the FTIR represented the alcohol group (hydroxyl) in the polyol sample. Main finding: Ethylene glycol successfully produced biopolyol according to the specified criteria as a suitable raw material for flexible polyurethane foam with a hydroxyl number of less than 100 mg KOH/g and an acid number of less than 2 mg KOH/g.